Evaluation of Mercury Contamination in Fungi Boletus Species from Latosols, Lateritic Red Earths, and Red and Yellow Earths in the Circum-Pacific Mercuriferous Belt of Southwestern China - Falandysz, Jerzy (PLoS One, 2015)
For the first time, highly elevated levels of mercury (Hg) have been documented for several species of the edible Fungi genus Boletus growing in latosols, lateritic red earths, and red and yellow earths from the Yunnan province of China. Analysis of Hg concentrations in the genus suggests that geogenic Hg is the dominant source of Hg in the fungi, whereas anthropogenic sources accumulate largely in the organic layer of the forest soil horizon. Among the 21 species studied from 32 locations across Yunnan and 2 places in Sichuan Province, the Hg was found at elevated level in all samples from Yunnan but not in the samples from Sichuan, which is located outside the mercuriferous belt. Particularly abundant in Hg were the caps of fruiting bodies of Boletus aereus (up to 13 mg kg(-1) dry matter), Boletus bicolor (up to 5.5 mg kg(-1) dry matter), Boletus edulis (up to 22 mg kg(-1) dry matter), Boletus luridus (up to 11 mg kg(-1) dry matter), Boletus magnificus (up to 13 mg kg(-1) dry matter), Boletus obscureumbrinus (up to 9.4 mg kg(-1) dry matter), Boletus purpureus (up to 16 mg kg(-1) dry matter), Boletus sinicus (up to 6.8 mg kg(-1) dry matter), Boletus speciosus (up to 4.9mg kg(-1) dry matter), Boletus tomentipes (up to 13 mg kg(-1) dry matter), and Boletus umbriniporus (up to 4.9 mg kg(-1) dry matter). Soil samples of the 0–10 cm topsoil layer from the widely distributed locations had mercury levels ranging between 0.034 to 3.4 mg kg(-1) dry matter. In Yunnan, both the soil parent rock and fruiting bodies of Boletus spp. were enriched in Hg, whereas the same species from Sichuan, located outside the mercuriferous belt, had low Hg concentrations, suggesting that the Hg in the Yunnan samples is mainly from geogenic sources rather than anthropogenic sources. However, the contribution of anthropogenically-derived Hg sequestered within soils of Yunnan has not been quantified, so more future research is required. Our results suggest that high rates of consumption of Boletus spp. from Yunnan can deliver relatively high doses of Hg to consumers, but that rates can differ widely because of large variability in mercury concentrations between species and locations.